Stability of upper face sexual dimorphism in central European populations (Czech Republic) during the modern age - Bejdová, Šárka; Dupej, Ján; Krajíček, Václav; Velemínská, Jana; Velemínský, Petr (International journal of legal medicine, 2018)
One of the most fundamental issues in forensic anthropology is the determination of sex and population affinity based on various skeletal elements. Therefore, we compared the sexual dimorphism of the upper facial skeleton from a recent Czech population (twenty-first century) with that of a population from Early Modern Age Bohemia (sixteenth to eighteenth centuries). Methods of geometric morphometrics were applied. According to the results, sexual dimorphism in terms of size, shape, and form was statistically significant in both populations. The best results of sex estimation originated from analyses of form. Thus, both size and shape differences should be taken into account for determination of the sex. The accuracy of prediction achieved 91.1% for individuals in the recent population and 87.5% for individuals from the early modern population. Only minor differences were found between sexual dimorphism in the studied populations. We conclude that sexual dimorphism of the upper facial skeleton is stable during the relatively short time period.
Keywords: Male; Support vector machine; lidé středního věku; anatomická značka; Geometric morphometrics; Skull; určení pohlaví podle kostry; Humans; Tomography, X-Ray Computed; počítačová rentgenová tomografie; Middle Aged; Czech Republic; Česká republika; mužské pohlaví; Female; Imaging, Three-Dimensional; Modern age population; obličejové kosti; Central Europe; zobrazování trojrozměrné; ženské pohlaví; Facial Bones; Sex estimation; support vector machine; mladý dospělý; Adult; Principal Component Analysis; Sex Determination by Skeleton; Young Adult; soudní antropologie; dospělí; lidé; Support Vector Machine; Forensic Anthropology; Anatomic Landmarks; lebka; Upper facial skeleton; analýza hlavních komponent